Toothless Lions of Agenda 2063 - DIARRA, Mohamed (The Pan African Sovereignty Network, 2025)
This article examines the African Union (AU) not as a neutral integration project, but as a functional component of the postcolonial control system. Building on earlier Pan-African critiques and recent psychopolitical models of “puppet governance,” it asks a precise question: does the AU ever act as an effective shield for African sovereignty when major external interests are at stake, or does it operate mainly as a continental alibi for neo-colonialism? Using cases from 2000 to 2025, the article maps AU reactions to four types of events: (1) asymmetric mining and corridor agreements; (2) foreign military bases and security deals; (3) externally backed coups and electoral fraud; and (4) structural debt arrangements that restrict policy space. It finds a consistent pattern. The AU rarely names or sanctions sitting governments for signing sovereignty-eroding treaties. It does not convene serious action on the “grooming pipelines” that train high-risk leaders abroad. It is quick to provide electoral legitimacy and photo-op diplomacy, yet silent when member states modify laws to favour foreign capital at the expense of local populations. The article formulates simple falsification tests for its core claim: one clear example of the AU blocking or reversing a major neo-colonial resource or corridor deal would challenge the “continental alibi” hypothesis. In the absence of such counter-examples, the evidence supports a harder conclusion. In its current funding structure and mandate, the AU stabilises a system that keeps Africa governable from outside. The paper ends by outlining minimal conditions for a truly sovereign continental body and by situating recent Sahel realignments and the DRC critical-minerals accords within this wider institutional diagnosis. Keywords African Union; Agenda 2063; Pan-Africanism; neo-colonialism; political institutions; sovereignty; critical minerals; security cooperation; Sahel; Democratic Republic of Congo